PENGARUH KELELAHAN EMOSIONAL DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN - Munira Lestaluhu; Ambarwati Soetiksno; Elsina Huberta Aponno (P3M Politeknik Negeri Ambon, 2023)
Initial survey at PT. Pelindo (Persero) Ambon Branch shows that there are indications of emotional exhaustion problems among employees. On the other hand, employees also show symptoms of work motivation. This research aims to find out how emotional fatigue and work motivation influence employee performance at PT. Pelindo (Persero) Ambon Branch.The analytical method used in this research is descriptive analysis and simple linear regression analysis. Descriptive analysis shows that emotional exhaustion of PT employees. Pelindo (Persero) Ambon Branch with an average value of 1,60 which is interpreted as very high, while work motivation with an average value of 2.16 is interpreted as low and employee performance with an average value of 2,85 The results of simple linear regression analysis show that emotional exhaustion has a negatif effect on employee performance and motivation has a positive effect on employee performance at PT. Pelindo (Persero) Ambon Branch.Based on these results, it can be concluded that the higher the emotional exhaustion and the lower the motivation, the employee performance will decrease. To overcome this PT. Pelindo (Persero) Ambon Branch must strive to reduce emotional exhaustion by paying attention to the symptoms of emotional exhaustion and work motivation that occur.Keywords: emotional exhaustion, work motivation, performance